(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
A search was carried out for natural plant growth stimulants that simultaneously have the properties of biopesticides. The experiment was carried out with isolates of microflora isolated from various natural objects of the Kyrgyz Republic. Microflora strains isolated from known biological products were used as analogues. The stimulating and fungicidal properties of the isolates were tested on tomato seeds of the Minibel variety